2023
DOI: 10.3390/agronomy13010249
|View full text |Cite
|
Sign up to set email alerts
|

Organo-Mineral Fertilization Based on Olive Waste Sludge Compost and Various Phosphate Sources Improves Phosphorus Agronomic Efficiency, Zea mays Agro-Physiological Traits, and Water Availability

Abstract: In the context of intensive and sustainable agriculture, limiting soil degradation and the loss of organic matter has become an obligation to maintain food security. The use of organo-mineral fertilizer (OMF) products is an innovative technology that may solve the different challenges raised. This study aimed to evaluate the effect of various organo-mineral fertilizer (OMF) formulations on Zea mays agro-physiological traits, phosphorus (P)-related parameters, and water conservation during a 90-day pot experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…This difference can be explained by the alkaline pH of the sludge and the nitrate content, which induced higher production of ammonia during the thermophilic phase, accelerating the increase in pH and the stability of the compost [24,25,51]. Bouhia [56] studied the composting process of olive mill waste sludge and green waste and reported similar changes in pH, with values that started at 5.5 and finally reached 7.9 after 120 days. It has been shown that changes in temperature and pH significantly affect decreases in ARG abundance and pathogen-host interactions (PHIs) in compost with chicken manure, indicating the vital role of these variables in the elimination of pathogenic microorganisms [57].…”
Section: Physicochemicalmentioning
confidence: 99%
“…This difference can be explained by the alkaline pH of the sludge and the nitrate content, which induced higher production of ammonia during the thermophilic phase, accelerating the increase in pH and the stability of the compost [24,25,51]. Bouhia [56] studied the composting process of olive mill waste sludge and green waste and reported similar changes in pH, with values that started at 5.5 and finally reached 7.9 after 120 days. It has been shown that changes in temperature and pH significantly affect decreases in ARG abundance and pathogen-host interactions (PHIs) in compost with chicken manure, indicating the vital role of these variables in the elimination of pathogenic microorganisms [57].…”
Section: Physicochemicalmentioning
confidence: 99%
“…VC is a kind of natural eco-manure, which is the product of organic matter degradation through the interaction between earthworms and microorganisms (10)(11)(12). As a result, VC is regarded a nutrient-dense biofertilizer with a diversi ed microbial community (13)(14). VC contains nutrients that are readily taken up by the plants, such as, available-P, K, Ca and Mg. VC is an excellent soil amendment or conditioner because of high porosity, aeration, drainage, waterholding capacity and microbial activity [15].…”
Section: Introductionmentioning
confidence: 99%
“…These fertilizers provide effective nutrients to plants and contribute to soil fertility and water retention [11]. The combination of organic and mineral materials allows for a gradual release of nutrients, promoting plant growth in terms of height, tiller number, and leaf area, resulting in high productivity performance [12].…”
Section: Introductionmentioning
confidence: 99%